2021
DOI: 10.1002/pssr.202000533
|View full text |Cite
|
Sign up to set email alerts
|

Area‐Selective Atomic Layer Deposition of MoS2 using Simultaneous Deposition and Etching Characteristics of MoCl5

Abstract: A novel selective atomic layer deposition (ALD) process for depositing MoS2 using MoCl5 and H2S precursors is proposed. On the surface of SiO2, the prolonged introduction of MoCl5 vapor by increasing the MoCl5 pulsing time rapidly suppresses the subsequent MoS2 growth due to the intense self‐etching effect of MoCl5, that is, the detachment of weakly bonded surface adsorbates (MoClx*). In contrast, the surface of Al allows more facile adsorption of MoCl5 than in the case of the SiO2 surface, and thus effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…An innovative approach proposed by Anh et al employs MoCl 5 and H 2 S precursors for selective ALD of MoS 2 . The mechanism for regioselective deposition is illustrated in Figure .…”
Section: The Ald Growth Strategy and Processes For The Synthesis Of Tmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…An innovative approach proposed by Anh et al employs MoCl 5 and H 2 S precursors for selective ALD of MoS 2 . The mechanism for regioselective deposition is illustrated in Figure .…”
Section: The Ald Growth Strategy and Processes For The Synthesis Of Tmdsmentioning
confidence: 99%
“…This technique also allows for selective growth on various transition-metal oxides and transition metal dichalcogenides (TMDs). Moreover, the promising outcomes of this study are expected to lay the groundwork for the regioselective ALD of other 2D materials.An innovative approach proposed by Anh et al83 employs MoCl 5 and H 2 S precursors for selective ALD of MoS 2 . The mechanism for regioselective deposition is illustrated in Figure14.…”
mentioning
confidence: 99%
“…An additional concern with the integration of 2D materials with CMOS technology is the difficulty in patterning the films, which will be critically damaged if exposed to plasma etching. A recent study by Ahn et al [ 198 ] showed that it was possible to simultaneously deposit and etch MoS 2 layers using MoCl 5 and H 2 S precursors at 400 °C. Essentially, the authors show a selective deposition process, whereby the Mo-precursor MoCl 5 would not adsorb onto the SiO 2 surface, while adsorbing onto the surface areas which were covered by aluminum, even after 400 ALD cycles, shown in Figure 15 .…”
Section: Fabrication and Working Principle Of 2d-material-based Gas S...mentioning
confidence: 99%
“… Schematic of the area-selective ALD process of MoS 2 showing the impact of the MoCl 5 pulse duration on the deposition of MoS 2 on different surfaces (SiO 2 and Al). (Reprinted with permission from Ahn et al [ 198 ]). …”
Section: Figurementioning
confidence: 99%
“…A few works have been reported for addressing this challenge. For example, Ahn et al presented an atomic layer deposition (ALD) method to enable area-selective deposition of MoS 2 through using MoCl 5 to suppress the MoS 2 nucleation on undesired regions . Huang et al demonstrated CVD-based selective growth of Sb 2 Te 3 features by using SiO 2 shadow masks .…”
Section: Introductionmentioning
confidence: 99%